A4NH 2020 annual report highlights: Flagship 5 - CGIAR Research Program on Agriculture for Nutrition and Health (International Food Policy Research Institute, 2021)
This includes three highlights document for Flagship 5 of the CGIAR Research Program on Agriculture for Nutrition and Health: Highlight 1: Launching a one health research center in Africa Highlight 2: Ensuring agricultural development supports the fight against malaria in Africa Highlight 3: Understanding the risk of future zoonotic outbreaks